The Relationship Between Self-Esteem and Resilience in Children Who Are Victims of Bullying - Cyndi, Ika Novita (PELNUS | Pen en Light for Natural Union of Science, 2024)
This study investigates the relationship between self-esteem and resilience in children who are victims of bullying. Drawing on a mixed-methods approach, the research examines quantitative data from a sample of 200 children aged 8 to 12 years, alongside qualitative insights from semi-structured interviews with a subset of participants. The findings reveal a significant positive correlation between self-esteem and resilience, indicating that higher self-esteem is associated with greater resilience in coping with the adverse effects of bullying. Additionally, qualitative analysis highlights the critical role of coping strategies and social support in enhancing both self-esteem and resilience. These results underscore the importance of fostering self-esteem as a protective factor for children facing bullying and emphasize the need for supportive environments that promote positive relationships. The implications for educators, mental health professionals, and policymakers are discussed, advocating for the implementation of programs and policies aimed at empowering children through the development of self-esteem and resilience. This research contributes to the understanding of the dynamics between self-esteem and resilience in the context of bullying, offering insights that can inform effective intervention strategies to support affected children.